Relationship between occupational factors and sleep disorders among petrochemical workers on Hainan Island, South China: a cross-sectional study - Qisheng Wu; Shiheng Fan; Bingxian Zhou; Chunyun Lu; Nengde Zhang; Zhuna Su; Jianye Peng; Dee Yu; Jing Zhang (International Journal of Occupational Medicine and Environmental Health)
Objectives The study aimed to examine the relationship between occupational factors and sleep disorders among employees in petrochemical enterprises.